Evaluation of Toxoplasma gondii recombinant proteins for the diagnosis of recently acquired toxoplasmosis by an immunoglobulin G analysis - Nigro, Monica (2003)
Fil: Nigro, Mónica. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas. Departamento de Parasitología; Argentina.